Multiple-Dose Study to Evaluate Pharmacokinetics, Pharmacodynamics, and Safety in Healthy Subjects: A Comparison of Controlled-Release Sarpogrelate and Immediate-Release Sarpogrelate - Lee, Soo-Yun; Kim, Jung-Ryul; Jung, Jin Ah; Kim, Tae-Eun; Lee, Soo-Youn; Huh, Wooseong; Lee, Jae-Won; Jun, Hun; Ko, Jae-Wook (Pharmacology, 2015)
Aims: To compare the pharmacokinetics, pharmacodynamics, and safety of sarpogrelate between controlled-release (CR) and immediate-release (IR) formulations after multiple-dose administration. Methods: This study was a randomized, open-label, 2-period, 2-treatment, crossover study in healthy subjects. All subjects received CR sarpogrelate 300 mg once daily and IR sarpogrelate 100 mg three times daily by random order each for 3 days with a 7-day washout period. Serial blood sampling was performed over 24 h. Pharmacokinetic parameters were determined by noncompartmental methods. Platelet aggregation to collagen, measured by light transmission aggregometry, was reported as maximal platelet aggregation. Results: Thirty-two subjects completed the study. CR sarpogrelate increased rapidly, reaching C max in 1.25 h (vs. 1.00 h in IR sarpogrelate) and declined with a t 1/2 of 3.59 h (vs. 1.12 h in IR sarpogrelate). The 90% CIs for the geometric mean ratio of AUC τ and C max,ss between IR and CR formulations were 1.18 to 1.40 and 0.99 to 1.29, respectively. The degree of inhibition of platelet aggregation was similar between two formulations. Conclusions: CR sarpogrelate showed slightly higher systemic exposure and similar peak concentration compared with IR sarpogrelate. The profiles of pharmacodynamics and safety were comparable between two formulations.